2020
DOI: 10.1590/2175-8239-jbn-2018-0169
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in nutritional parameters and resting energy expenditure in end-stage renal disease

Abstract: Aims: To evaluate the nutritional status, resting energy expenditure, caloric and protein intake, and evolution of biochemical parameters in three stages of chronic kidney disease: pre-dialytic, at the beginning of the dialysis treatment, and 30 days after starting treatment. Methods: The chi-square and Student’s t tests were used to compare the variables, and analysis of repeated measurements was used to compare the data obtained in the three moments evaluated. The results were discussed at the 5% level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…After discussion, the main reason for the difference between this research and the previous results is that the patients also received HD treatment during the rs-fMRI examination. Oliveira et al [ 27 ] used the low-frequency oscillation amplitude algorithm to research the fMRI of ERSD patients during HD treatment and found the difference between the ESRD patient group and the healthy control group was not obviously connected with SCr and BUN. The reason for this result may be that the SCr and BUN levels of ESRD patients are controlled at relatively stable values during regular HD, and the brain activity of ESRD patients has a certain tolerance to long-term high SCr and bun levels.…”
Section: Discussionmentioning
confidence: 99%
“…After discussion, the main reason for the difference between this research and the previous results is that the patients also received HD treatment during the rs-fMRI examination. Oliveira et al [ 27 ] used the low-frequency oscillation amplitude algorithm to research the fMRI of ERSD patients during HD treatment and found the difference between the ESRD patient group and the healthy control group was not obviously connected with SCr and BUN. The reason for this result may be that the SCr and BUN levels of ESRD patients are controlled at relatively stable values during regular HD, and the brain activity of ESRD patients has a certain tolerance to long-term high SCr and bun levels.…”
Section: Discussionmentioning
confidence: 99%
“…Achados nos estudos de Avesani et al 15 e Ikizler et al 16 demonstraram que há um aumento do gasto energético e catabolismo proteico em pacientes submetidos a HD. É preciso, além de atentar-se ao consumo energético para evitar prejuízos nutricionais 17 , considerar a globalização alimentar, visando à alimentação saudável, respeitando a subjetividade de cada indivíduo 7 . A recomendação proteica é de 1,2 g/kg/dia em pacientes em HD 10 , sendo um achado relevante nesse estudo, já que o consumo adequado de proteína estava adequado nos dois grupos.…”
Section: Discussionunclassified
“…A recomendação deve ser feita de forma individualizada e seguir a indicação <2,3 g/dia, analisando se existem perdas como as gastrointestinais (vômito e diarreia) e intervenções farmacológicas adequadas 10 . Apesar de não ser verificada a existência da hipertensão arterial sistêmica (HAS) nos indivíduos desse estudo, é claro na literatura que é corriqueiro que pacientes em HD apresentem HAS, uma vez que é um fator de risco para DRC 17 . Diante isso, o controle da pressão arterial faz parte do sucesso do tratamento clínico da DRC.…”
Section: Discussionunclassified
“…PEW characteristics were standardized in 2008 by the International Society for Renal Nutrition and Metabolism, which divided PEW into further groupings, mainly: abnormal serum biochemistry, reduced body mass, reduced muscle mass and unintentional low dietary intake [ 25 ]. Weight loss, an indicator of malnutrition, has been reported in patients undergoing PD therapy despite increases in caloric intake and unaltered activity levels [ 26 ]. An observational study conducted by Dong et al, assessed the impact of PEW on survival.…”
Section: Significance Of Nutritional Status In Pdmentioning
confidence: 99%